1999
DOI: 10.1103/physrevc.60.024601
|View full text |Cite
|
Sign up to set email alerts
|

d/pandt/pratios in nucleon-nucleus and heavy ion reactions: Can entropy be determined?

Abstract: The relative yields of high energy deuterons and tritons as compared to protons have been measured in p ϩKr, 16 OϩKr and 20 NeϩAr reactions with a continuously varying beam energy up to 500A (400A) MeV. Statistical ͑expanding͒ evaporation models are not able to reproduce these d/p or t/p ratios, which for high particle energy (Ͼ30 MeV) increase smoothly with beam energy. Models that contain nucleon-nucleon scattering, like cascade or nuclear molecular dynamics models, can only reproduce the ratios if a final-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Recently, the CHIC Collaboration [9] measured the yields of d/p and t/p in asymmetric collisions of p + Kr, O + Kr, and Ne + Ar. The statistical evaporation models were reported to fail to reproduce these ratios [9]. The microscopic and mean-field calculations, on the other hand, could explain the data nicely.…”
mentioning
confidence: 99%
“…Recently, the CHIC Collaboration [9] measured the yields of d/p and t/p in asymmetric collisions of p + Kr, O + Kr, and Ne + Ar. The statistical evaporation models were reported to fail to reproduce these ratios [9]. The microscopic and mean-field calculations, on the other hand, could explain the data nicely.…”
mentioning
confidence: 99%
“…Such behavior is believed to be resulted from the coalescence production mechanism [6,7]. Experimentally, the study of d/p ratios obtained in asymmetric collisions of p+Kr, O+Kr, and Ne+Ar also indicates the importance of coalescence mechanism [8]. In this study, it was observed that d/p ratio increases with the beam energy.…”
Section: Introductionmentioning
confidence: 50%
“…The property of preserving the early traces and unaltered behavior in the expansion phase of compressed state of nuclear matter gives one the obvious reason to study entropy as a crucial parameter. Various valuable theoretical and experimental attempts have been done in the past to study the entropy production [18][19][20][21][22][23][24][25][26]. For example, Doss et al [21] measured the yield ratios for lighter fragments and entropy for the reactions of 40 Ca+ 40 Ca and 93 Nb+ 93 Nb at incident energies of 400 and 600MeV/nucleon, respectively.…”
Section: Introductionmentioning
confidence: 99%